Nanotopograpical Analysis of Iron by AFM - Dahal, N P; Lamichhane, S K (Himalayan Physics, 2011)
The roughness of the surface is sensed by the cantilever deflection of AFM, more the roughness of the surface greater will be the deflection and vice versa. The roughness of iron obtained from the AFM is depending upon the sanning area. The roughness of the surface can be studied from the analysis of the height profile and nano topography of the etched iron by AFM. Key words: Etching; AFM; Topography; Probe The Himalayan Physics Vol. 2, No.2, May, 2011 Page: 73-75 Uploaded Date: 1 August, 2011